Gene 18s rRNA variation of cuttlefish population (Sepia pharaonis) in the Persian Gulf and the Oman Sea using PCR-RFLP method - R. Nahavandi; S. Rezvani; Gh. Vosoghi; B. Kazemi (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2005)
We used PCR-RFLP method to identify cuttlefish (Sepia pharaonis) populations in the Persian Gulf and the Sea of Oman. Bottom trawling method was used to collect a range of 20 to 40 specimens from each 15 stations in the study area. Genomic DNA was extracted by phenol-chloroform method and one pair primer was designed for the analysis based on 18s rRNA gene nucleotide sequences. A PCR product with 502 pair bases in length was obtained for all specimens and subjected to digestion by eight restriction enzymes Alu1, were similar and no polymorphism was detected among them. We conclude that cuttlefish populations cannot be isolated using 18s rRNA gene extracts in the area of study.